Upaya Peningkatan Kompetensi Profesionalisme Guru Pendidikan Dasar Dalam Proses Pembelajaran - Eti Dwi Koriati; Aldo Redho Syam; Ayok Ariyanto (AL-ASASIYYA: Journal Of Basic Education, 2021)
The professional competence of elementary school teachers plays an important role in the learning process in schools. The professional competence of elementary school teachers must still refer to actions that are rational and have certain specifications in carrying out educational tasks. Elementary school teachers as professional staff are required to have the abilities and skills in accordance with the fields they are engaged in so that the potential growth and development process of students which includes cognitive, affective, psychomotor, and spiritual aspects can run well and in accordance with the educational goals that have been set. set. This study uses a qualitative-descriptive approach with critical discourse analysis methods and literature review from several comprehensive literature and journals. Based on the results of the study, it can be concluded that efforts to increase the professional competence of elementary school teachers can be carried out through the following steps: first, the efforts made by elementary school teachers to improve their professional competence, including: attending teacher upgrading, training, workshops, national or international seminars , and deliberations of teachers in the field of study, increasing knowledge through mass or electronic media, and professional improvement through independent study; and second, the efforts made by school principals in increasing the professional competence of elementary school teachers, including: empowering the professionalism of elementary school teachers through collaboration with advanced and developing elementary school institutions, providing opportunities for elementary school teachers to improve their profession, encouraging teacher involvement elementary school in every school education activity (participatory), and increasing the knowledge of elementary school teachers through deliberation, both among material teachers and as a whole.